Determinants of Bank Stability in Indonesia - Rahmatina Awaliah Kasri; Chairilisa Azzahra (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This study aims to analyse the determinant of banks’ stability in Indonesia, which is very important to ensure that the country’s banking system could be more effective in supporting transmission of monetary policy and more resilient in facing financial crisis. To achieve the objective, this study collected a comprehensive dataset from 94 banks in Indonesia, covering both conventional and Islamic banks, during September 2015 - June 2019 period. The data is subsequently analysed by employing dynamic panel data model. The results show that the main factors that positively influenced banks’ stability in Indonesia are exchange rate, financial inclusion, asset returns, and credit/financing growth. However, interest rates are found to be negatively influenced the stability. The findings are expected to provide insights for policy makers and market players in ensuring that the banks’ stability could be well maintained in Indonesia. The results are also hoped to enrich literature in economics and banking, particularly in emerging markets like Indonesia.JEL Classification: G21.How to Cite:Kasri, R. A., & Azzahra, C. (2020). Determinants of Bank Stability in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 153-166. doi: http://doi.org/10.15408/sjie.v9i2.15598.